Factors Associated with Incomplete Insertion of Electrodes in Cochlear Implant Surgery: A Histopathologic Study - Lee, Joonhan (S. Karger AG, 2011)
OBJECTIVES: Atraumatic and complete insertion of the electrode array is a stated objective of cochlear implant surgery. However, it is known that obstructions within the cochlea such as new bone formation, cochlear otosclerosis, temporal bone fracture, and cochlear anomalies may limit the depth of insertion of the electrode array. In addition, even among patients without obvious clinical or radiographic indicators of obstruction, incomplete insertion may occur. The current study is a histopathologic evaluation of possible sources of resistance to insertion of the electrode array using the temporal bone collection of the Massachusetts Eye and Ear Infirmary. METHODS: Forty temporal bones from patients who in life had undergone cochlear implantation were evaluated. Temporal bones were removed at autopsy and fixed and prepared for histologic study by standard techniques. Specimens were then serially sectioned and reconstructed by 2-dimensional methods. Two electrode metrics were determined for each bone: the inserted length (IL: the distance measured from the cochleostomy site to the apical tip of the electrode) and the active electrode length (AEL: the distance between the most basal and most apical electrodes on the electrode array). The ratio of these two metrics (IL/AEL) was used to split the temporal bones into two groups: those with incomplete insertion (n = 27, IL/AEL <1.0) and those with complete insertion (n = 13, IL/AEL ≥1.0). Seven possible histopathologic indicators of resistance to insertion of the electrode due to contact with the basilar membrane, osseous spiral lamina and/or spiral ligament were evaluated by analysis of serial sections from the temporal bones along the course of the electrode tracks. RESULTS: Obvious obstruction by abnormal intracochlear bone or soft tissue accounted for only 6 (22%) of the 27 partial insertions. Of the remaining 21 bones with incomplete insertions and 13 bones with complete insertions, dissection of the spiral ligament to the lateral cochlear wall was the only histopathologic indicator of insertion resistance identified with significantly higher frequency in the partial-insertion bones than in the complete-insertion bones (p = 0.003). An observed trend for the percentage of complete insertions to decrease with the number of times the electrode penetrated the basilar membrane did not reach significance. In the bones without an obvious obstruction, the most frequently observed indicator of insertion resistance was dissection of the spiral ligament (with no contact of the lateral cochlear wall) identified in 67% (14/21) of partial-insertion bones and in 92% (12/13) of complete-insertion bones. CONCLUSION: These results are consistent with the view that (1) electrode contact with cochlear structures resulting in observable trauma to the basilar membrane, osseous spiral lamina and/or spiral ligament does not necessarily impact the likelihood of complete insertion of the electrode array and (2) once contact trauma to the spiral ligament reaches the point of dissection to the cochlear wall, the likelihood of incomplete insertion increases dramatically.